Assessment of dissolved oxygen and ecological impact of carbon dioxide in the Bhogdoi River, Jorhat, Assam - Karmakar, Panchali (Journal of Advanced Education and Sciences, 2026)
The Bhogdoi River, a crucial south-bank tributary of the Brahmaputra River, is essential for the ecological and socio-economic aspects of Jorhat district, Assam. Recently, factors such as rising urban development, runoff from agriculture, discharge of household sewage, and uncontrolled disposal of solid waste have greatly impacted the quality of the river’s water. This current research examines the levels of dissolved oxygen (DO) and the ecological effects of dissolved carbon dioxide (CO₂) within the river’s surroundings. Water samples were taken from three chosen monitoring locations that represented the upstream, urban, and downstream areas of the river. The dissolved oxygen levels were found to range from 5.4 to 8.5 mg/L, demonstrating moderate to good oxygen presence for aquatic life. The upstream areas displayed higher concentrations of DO, while the urban location showed relatively lower levels, indicating the effects of organic pollution and increased microbial growth. Dissolved carbon dioxide levels differed across the sampling locations, being notably higher in regions influenced by domestic and agricultural runoff. Increased CO₂ levels can change the pH of the water, decrease its buffering ability, and indirectly hinder oxygen availability by promoting microbial respiration. The link between reduced DO and elevated CO₂ at the urban site signifies the effect of human activities on river ecosystems. While the river still provides conditions that favor aquatic organisms, ongoing pollutant influx could potentially lead to a decline in its ecological balance. This study emphasizes the necessity of consistent monitoring of dissolved oxygen and carbon dioxide as vital measures of freshwater ecosystem health. Efficient waste management and preservation methods are critical for safeguarding the Bhogdoi River and ensuring its ecological viability over time.